Student Athletes And Teacher Coaches’ Taekwondo Participation As Strategy On Leisure And Life Satisfaction And Promotion Of Physical Fitness - Umang, Gerald; Mortejo, Alonzo L (International Martial Arts and Culture Journal, 2023)
Background and aim. Taekwondo participation among student athletes and teacher coaches is viewed as a strategic approach to enhancing serious leisure, life satisfaction, and physical fitness. However, evidence supporting this role in the educational context remains limited. Therefore, this study aimed to examine whether taekwondo participation is associated with leisure, life satisfaction, and the promotion of physical fitness.Methods.  A descriptive correlational research design was employed in this study. Data were collected using interview and observation techniques developed through an extensive review of relevant literature, including books, journals, research articles, theses, and dissertations related to student athletes and sports engagement.Results.  The findings revealed a significant association between student athletes’ satisfaction with leisure and lifestyle promotion and teacher coaches’ job satisfaction. However, no significant relationship was found between the promotion of student athletes’ physical health and the coaching provided by teachers.Conclusions.      Teacher coaches are encouraged to emphasize comprehensive taekwondo training programs that frame taekwondo as a form of serious leisure and lifestyle, thereby enhancing student athletes’ engagement and overall satisfaction.